2017
DOI: 10.1055/s-0037-1600116
|View full text |Cite
|
Sign up to set email alerts
|

Do Flow and Pulsatility Index within the Accepted Ranges Predict Long-Term Outcomes after Coronary Artery Bypass Grafting?

Abstract: Transit-time flow measurement (TTFM) is the gold standard for intraoperative detection of graft failure. Several reports show that TTFM and distal coronary bed quality (DCBQ) may also be useful for midterm detection of graft failure. Nonetheless, there are no data regarding their predictive role on long-term outcomes. Patients with three-vessel disease who underwent isolated coronary artery bypass grafting (CABG) in 2006 and received at least one graft to the left anterior descending artery (LAD) or to the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Twelve studies evaluated short-term outcomes in relation with TTFM parameters (Supplementary Material, Table S4) [8, 13, 25, 27, 54, 62, 69, 71–75]. Bauer et al [75] compared CABG with TTFM versus without TTFM and found an increased rate of intraoperative redo-anastomoses, which coincided with significantly lower incidences of ventricular fibrillation, perioperative MI and postoperative mortality when TTFM was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies evaluated short-term outcomes in relation with TTFM parameters (Supplementary Material, Table S4) [8, 13, 25, 27, 54, 62, 69, 71–75]. Bauer et al [75] compared CABG with TTFM versus without TTFM and found an increased rate of intraoperative redo-anastomoses, which coincided with significantly lower incidences of ventricular fibrillation, perioperative MI and postoperative mortality when TTFM was performed.…”
Section: Resultsmentioning
confidence: 99%
“…However, observational studies showed the positive predictive capability of TTFM on intermediate-term clinical outcomes, such as major adverse cardiac events, mortality, intra-aortic balloon pump placement or cardiac enzyme release [8, 75]. Other studies reported data that showed no correlation between TTFM parameters and mid-term hospital readmission (during 1.8-year follow-up) [25], survival after 3.8 years [74] or even long-term survival (7.8 ± 0.2 years, Supplementary Material, Table S4) [13].…”
Section: Resultsmentioning
confidence: 99%
“…8,20 Several studies have shown no correlation between TTFM and clinical outcomes. 21,22 However, Kieser and colleagues 23 reported a correlation between PI values and postoperative major adverse cardiac events but had a greater overall mortality of 4.8% than typically anticipated. 23 The randomized Graft Imaging to Improve Patency (GRIIP) trial 22 found no differences in graft failure at 1 year by coronary angiography between the control group and patients who underwent intraoperative TTFM.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown no correlation between TTFM and clinical outcomes. 21 , 22 However, Kieser and colleagues 23 reported a correlation between PI values and postoperative major adverse cardiac events but had a greater overall mortality of 4.8% than typically anticipated. 23 …”
Section: Discussionmentioning
confidence: 98%
“…Thus far, most TTFM assessment studies have focused largely on its association with patency. As with the REQUEST study, few studies examined clinical outcome 17,18 and most are limited by the lack of a concurrent comparison group. An exception is the study by Singh and colleagues 6 that randomly allocated 156 patients to two equal groups, comparing TTFM use and nonuse.…”
Section: Commentmentioning
confidence: 99%